Strategies for Developing Teacher's Competency Innovator under the Office of the Basic Education Commission - Kamyos, Woranidtha; Umnuayrat , Sopa; Khlaium, Sunthorn; Gunma , Namfon (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research has objectives 1) study the composition and current state of teachers' innovator competencies 2) study guidelines for developing teacher's innovator competencies 3) create strategies developing teacher's innovator competencies and 4) study results of the evaluation of strategies for developing teacher's innovator competencies. The research method has 4 steps: Step 1: Study of components and indicators by synthesizing relevant documents research and study the current condition, sample group consisted of 375 educational institution administrators, obtained by multi-stage random sampling, collect data using a 5-level rating scale questionnaire, reliability 0.92, analyzed with average and standard deviation. Step 2: Study guidelines for development teacher's innovator competencie with 7 experts, with a semi-structured interview, analyzed with content analysis. Step 3: Creating a strategy by studying the environment (SWOT Analysis) with a group of 25 people giving information and using information from step 1 and 2 let's draft a strategy (TOWS Matrix) and check by group discussion with 9 experts. Step 4: Strategy evaluation of 56 educational institution administrators, collect data using a 5-level rating scale questionnaire, reliability 0.97, analyzed with average and standard deviation. The results of the research found that 1) The results of the study of the components consists of 6 elements as follows: creativity asking questions, experimenting, knowledge and practice, personal personality and the creation of social networks 2) Results of the study of guidelines for developing teachers' innovator competees strategy should be set mission, goals, ecosystem with digital technology and the current state of teachers' innovative competencies the overall is at a moderate level 3) Results of creating strategies for developing teachers' innovative competencies consisting of vision, mission, 6 main strategies, 26 sub-strategies and the overall is appropriate at a high level and 4) Results of the evaluation found that possible and usefulness is at the highest level.